Feminist Standpoint Theory (A Case Study of Mulyana from a Radical Feminist Perspective: Violence Against Women) - Nafadillah, Aiska Twinta; Despriyanti, Nabila Jalu Putri; Anggraini, Anisa Dwi; Maulina, Nadia Antika; Addin, Mochammad Fachrial Aura Hilmi (Journal of Media and Digital Society on SDGs, 2025)
In this research, we examine the media representation of cases of gender-based violence committed by Mulyana against her partner, Siti Amelia, using a qualitative approach and descriptive analysis methods. The main focus of this study is how online media constructs narratives related to chronology, motives of perpetrators, and how information is conveyed in the news. The results of the study show that the media tends to highlight sensational aspects such as the alleged pregnancy of the victim without delving in depth into the structural roots of the violence, such as the patriarchal system and gender inequality. And it was also found that there was a tendency in the news to indirectly corner the victims. This case shows that femicide is not just a criminal act, but a real manifestation of male domination over women’s bodies and identities in a patriarchal society. Therefore, a feminist approach in reporting as well as social and cultural transformation is very necessary to prevent similar violence in the future. Key words: femicide, gender inequality, patriarchy, media representation, feminism